Signaling Circuitries Controlling Stem Cell Fate: To Be or Not To Be - Iglesias-Bartolome, Ramiro (2011)
The integration of extrinsic and intrinsic signals is required to preserve the self-renewal and tissue regenerative capacity of adult stem cells, while protecting them from malignant conversion or loss of proliferative potential by death, differentiation or senescence. Here we review emerging signaling circuitries regulating stem cell fate, with emphasis on epithelial stem cells. Wnt, mTOR, GPCRs, Notch, Rho GTPases, YAP and DNA and histone methylases are some of the mechanisms that allow stem cells to balance their regenerative potential and the initiation of terminal differentiation programs, guaranteeing appropriate tissue homeostasis. Understanding the signaling circuitries regulating stem cell fate decisions might provide important insights into cancer initiation and numerous human pathologies that involve the progressive loss of tissue-specific adult stem cells.